(untitled) (Italian Journal of Public Health, 2006)
Background: In the European Union, work-related stress affects about one in four workers, and it may be responsible for the loss of productivity, healthcare consumption and absenteeism. The objective of our study was to estimate whether stress programmes aimed at managing and preventing work-related stress reduced the rate of absenteeism. Methods: We searched electronic databases for relevant articles assisted by hand searching for references. We included studies that had an experimental or quasi-experimental design, describing an intervention focused either on the work organisation or on workers’ characteristics as well as reporting a measure of absenteeism. Results: The search identified 2520 articles: among these, nine met our inclusion criteria. Stress management programmes reduced absenteeism shortly after the intervention however in the long term there was no evidence to support this. Conclusion: Future studies should evaluate stress management programmes that consist of repeated interventions over longer periods of time, focusing on effectiveness and relative costs.